Nilai Kearifan Lokal dalam Tradisi Pindah Rumah Baru pada Masyarakat Sintang Kalimantan Barat - Nazlah Saskia Humayira; Syarifah Elisa Idrus (Jurnal Studi Pendidikan Agama Islam, 2025)
house among the Sintang community in West Kalimantan. The research employs a qualitative approach using a phenomenological method, which focuses on understanding the meaning of the community’s social experiences related to this tradition. This approach is chosen to explore the perspectives, interpretations, and subjective experiences of the community in practicing the new house–moving tradition as an integral part of their social and cultural life. Data collection techniques include in-depth interviews with informants who are considered knowledgeable about the tradition, as well as member checking to ensure the validity and accuracy of the data obtained. The main focus of this study is to understand the role and meaning of the new house–moving tradition in the social life of the Sintang community, while also identifying the cultural values and local wisdom embedded within it.The findings reveal that the tradition of moving into a new house is not merely understood as a physical relocation process, but also as a social event rich in cultural meaning. This tradition reflects strong social solidarity, a sense of togetherness, and respect for ancestors that are still highly upheld by the community. The practice of mutual cooperation (gotong royong) serves as the main foundation in every stage of the tradition, while customary practices and distinctive cultural symbols of Sintang provide profound meaning to the procession. In addition, neighborly relations play a central role in maintaining community harmony, and the selection of the new house location is also influenced by local environmental values believed by the community. Thus, this study offers a comprehensive understanding of local wisdom in the tradition of moving into a new house among the Sintangcommunity and emphasizes the importance of understanding and preserving traditions as an integral part of the cultural identity of the people of West Kalimantan.